PEMANFAATAN LIMBAH ROTI MENJADI PRODUK YANG BERNILAI GUNA MENUJU PENERAPAN CIRCULAR ECONOMY - Anita, Anita (Asosiasi Dosen Muda Indonesia, 2023)
Bread is one of the products that are mostly produced by small and medium industries (SMEs). Along with the increase in bread production by SMEs, it has the potential to cause many environmental problems. The main environmental problems faced by the bread industry are waste management, efficient use of materials, water and energy during the production process. One solution that can be done to solve these problems is through the application of the circular economy concept. This research aims to study the production process of various flavours of bread and analyse the potential application of the circular economy concept for the development of a sustainable bakery industry by utilising bread waste into valuable products, and to learn how waste is handled in the bakery industry. The research was conducted through field observations and literature studies. The research data were processed, analysed and presented descriptively qualitatively. The results of the study show that the concept of circular economy that can be adopted in the bakery industry such as the utilisation of solid waste in the form of pieces of peeled white bread and unsold bread scraps, as animal feed ingredients.